Evaluation of Mortality of Patients with Neonatal Tetanus - Taslim S. Soetomenggolo; Hardiono D. Pusponegoro; Jimmy Passat; Sofyan Ismael (Indonesian Pediatric Society, 1994)
During 8 years, 405 patients of neonatal tetanus were hospitalized in the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta. Diagnosis of neonatal tetanus was based on clinical signs and symptoms. Of the 405 patients, 56.3% were males and 43.7 %. were females. Two hundreds and sixty nine (66.3 %) patients were delivered by traditional birth attendants, and only 33.6% were delivered by midwives or physicians. The overall mortality was 54.4%, with the corrected mortality of 46.7%. Severity of the disease, short incubation period, short period of onset, and the accompanying diseases were responsible for the high mortality of patients with neonatal tetanus.